Childhood obesity is associated with shorter leukocyte telomere length. - Buxton, J; Walters, R; Visvikis-Siest, S; Meyre, D; Froguel, P; Blakemore, A (2011)
CONTEXT: Obesity in adults is associated with shorter mean leukocyte telomere length (LTL), a marker of biological age that is also associated with age-related conditions including cardiovascular disease and type 2 diabetes. However, studies of childhood obesity and LTL have proved inconclusive. OBJECTIVE: The objective of the study was to clarify the relationship between telomere length and childhood obesity by measuring the average LTL in a large case-control cohort. PARTICIPANTS AND METHODS: LTL was measured in 793 French children aged 2-17 yr (471 with early onset obesity and 322 nonobese controls) using multiplex quantitative real-time PCR. The average LTL in the two groups was compared, and the relationships between telomere length and selected anthropometric and biochemical measurements were examined. RESULTS: Obese children had a mean LTL that was 23.9% shorter than that of nonobese children (P < 0.0001). Telomere length was inversely associated with age (R = -0.17, P = 0.002 in controls; R = -0.15, P = 0.001 in cases), log weight (R= -0.13, P = 0.017 in controls; R = -0.16, P = 0.0004 in cases), and height (R = -0.15, P = 0.008 in controls; R = -0.17, P = 0.0002 in cases). The mean LTL of girls and boys was not significantly different in either the cases or controls or in the group overall. CONCLUSION: Obese girls and boys have significantly shorter leukocyte telomeres than their nonobese counterparts, a finding that highlights a potentially deleterious impact of early onset obesity on future health.